Non-Permanent Transcatheter Proximal Renal Artery Embolization for a Grade 5 Renal Injury with Delayed Recanalization and Preserved Renal Parenchymal Enhancement - Abhishek Jairam; Bradley King; Zachary Berman; Gerant Rivera-Sanfeliz (Journal of Trauma and Injury)
Super-selective renal artery embolization is an increasingly popular technique for the management of traumatic, low-grade renal trauma. When performed in distal arterial branches, this intervention enables tissue preservation and arrest of hemorrhage, but it may not be practical in cases of multifocal, high-grade renal injuries. In such cases, surgical nephrectomy remains the more common treatment modality to ensure hemodynamic control. We present the unique case of a patient who presented in hemorrhagic shock following a major trauma that resulted in a grade 5 renal injury treated with complete renal artery embolization using Gelfoam, resulting in hemodynamic stabilization. Interestingly, imaging 1 month after embolization revealed residual enhancement of the inferior pole of the kidney, suggesting reconstitution of flow and partial renal salvage. Ultimately, transcatheter “nephrectomy” with careful selection of a temporary embolic agent may serve as a safe and efficient alternative to surgical nephrectomy with the added possibility of preserving partial renal perfusion and function in the emergent setting.